Association between variation in the genes DDAH1 and DDAH2 and hypertension among Uygur, Kazakh and Han ethnic groups in China - Wang, Zhong; Chen, Shaoze; Zhang, Lina; Lu, Guilin; Zhou, Chengming; Wang, Dao Wen; Wang, Li; Badengmu, Bayinbate; Zhai, Zhihong; Qin, Lian (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Dimethylarginine dimethylaminohydrolase enzymes (DDAH), which are encoded by the genes DDAH1 and DDAH2, play a fundamental role in maintaining endothelial function. We conducted a case-control study on a Chinese population that included three ethnic groups (Han, Kazakh and Uygur), to systemically investigate associations between variations in the genes DDAH1 and DDAH2 and hypertension. DESIGN AND SETTING: Experimental study at the Department of Internal Medicine and Genetic Diagnosis, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology. METHODS: This case-control study included 1,224 patients with hypertension and 967 healthy unrelated individuals as controls. DDAH1 -396 4N (GCGT) del>ins, rs3087894, rs805304 and rs9267551 were genotyped using the TaqMan 5’ nuclease assay. RESULTS: The G/C genotype of rs3087894 in DDAH1 was a risk factor for hypertension in the Kazakh group in the co-dominant model (G/C versus G/G) (OR 1.39; 95% CI: 1.02-1.88; P < 0.05), with the same result in the dominant model (G/C + C/C versus G/G) (OR 1.38; 95% CI: 1.03-1.84; P < 0.05). In contrast, the C/C genotype of rs3087894 seemed to be a protective factor against hypertension in the Uygur group in the recessive model (C/C versus G/G + G/C) (OR 0.62; 95% CI: 0.39- 0.97; P < 0.05). Similar findings for rs3087894 were also observed after adjusting the variable for the age covariate. CONCLUSION: Our results indicated that the C-allele of rs3087894 in DDAH1 was a risk factor for hypertension in the Kazakh group but a protective factor in the Uygur group.